Seasonal trend in movement directions at dawn and dusk: a study on crow and white herons. Issue 4 (3rd July 2016) - Kumar, Raj; Singh, Devraj; Rani, Sangeeta; Malik, Shalie
Abstract: Crows ( Corvus splendens ) and white herons ( Ardea alba ) inhabit the agricultural landscapes nearby human habitats which represent dynamic ecosystem and show seasonal crop patterns. We studied the movement pattern in these birds at dawn and dusk, during solstices (December and June) and equinoxes (March and September). The movement directions were changed from uniform at dawn to a concentrated distribution at dusk all along the season suggesting that morning movements are more exploratory than evening with seasonal differences. Differential use of directions in December than June could be the effect of temperature, food availability or wind direction and speed. During breeding, less number of directions used suggests that birds might be moving towards the directions having high probability of food availability. It is likely that avian dispersal in space and time is dependent on the food availability however, further studies are required to be carried out.